Investigation of the electrical and optical properties of InAs/InGaAs dot in a well solar cell - Lee, Seung Hyun; Han, Im Sik; Sohn, Chang Won; Jo, Hyun-Jun; Kim, Jong Su; Lee, Sang Jun; Noh, Sam Kyu; Kim, Jun Oh (Current applied physics, 2015)
The electroreflectance (ER) and current–voltage (J–V) of InAs/InGaAs dots in a well (DWELL) solar cell (SC) were measured to examine the optical and electrical properties. To investigate the carrier capturing and escaping effects in the quantum dot (QD) states the above and below optical biases of the GaAs band gap were used. In the reverse bias region of the J–V curve, the tunneling effect in the QD states was observed at low temperature. The ideality factors (n) were calculated from the J–V curves taken from various optical bias intensities (Iex). The changes in the ideality factor (n) and short circuit current (JSC) were attributed mainly to carrier capture at low temperature, whereas the carrier escaping effect was dominant at room temperature. ER measurements revealed a decrease in the junction electric field (FJ) due to the photovoltaic effect, which was independent of the optical bias source at the same temperature. At low temperature, the reduction of photovoltaic effect could be explained by the enhancement carrier capturing effect due to the strong carrier confinement in QDs. •The properties of InAs/InGaAs dot in a well (DWELL) solar cell (SC) were studied.•The electrical property was investigated using current–voltage (J–V) measurement.•The optical property was investigated using electroreflectance (ER) measurement.•The above and below optical biases of the GaAs band gap were adopted.•The results are explained by the carrier processes such as capturing and escaping.